1995
DOI: 10.1007/bf01464470
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic study of endogenous peroxidase activity in human liver macrophages

Abstract: We evaluated the conditions of fixation for ultrastructurally demonstrating the endogenous peroxidase (PO) activity of macrophages in biopsied human liver. The application of microwaving and immersion fixation with tannic acid and aldehydes allowed excellent visualization of PO activity in the nuclear envelope (NE), rough endoplasmic reticulum (rER), and cytoplasmic granules (CG), with good preservation of cellular ultrastructures. The macrophages with PO activity showed one of the following five patterns of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The toxicological significance to these findings would be primarily dependent upon physiological constraints such as location and pH. Using an electron microscopy technique, it has been shown that endogenous peroxidase activity exists in hepatic macrophage rough endoplasmic reticulum, nuclear envelope, and cytoplasm (29). Prostaglandin H synthase, another type of peroxidase, also resides within the endoplasmic reticulum which is contiguous with the nuclear membrane (30).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicological significance to these findings would be primarily dependent upon physiological constraints such as location and pH. Using an electron microscopy technique, it has been shown that endogenous peroxidase activity exists in hepatic macrophage rough endoplasmic reticulum, nuclear envelope, and cytoplasm (29). Prostaglandin H synthase, another type of peroxidase, also resides within the endoplasmic reticulum which is contiguous with the nuclear membrane (30).…”
Section: Discussionmentioning
confidence: 99%
“…They readily phagocytose latex beads [96] and express a variety of macrophage related scavenger receptor molecules [40,69]. However, there is clearly variability in the expression of these markers and other molecules amongst KCs and light [32] and electron [86] microscopy findings have identified that KCs are composed of differing subsets of cells, which are distributed through different zones of the liver lobule. These findings indicate that KCs appear to be heterogeneous, but exploration of KC subset composition and function is lacking.…”
Section: Kupffer Cells Appear To Be Heterogeneousmentioning
confidence: 94%
“…In 1995, Ueda et al [86] described KC functional heterogeneity based on endogenous peroxidase activity that divided the cells into monocytes and four types of macrophages that showed a zonal distribution. These findings suggest that KCs are a collection of cells with varying phenotypes throughout different parts of the healthy liver, which is a concept that has been further supported by work in chronically hepatitis C virus infected livers [16].…”
Section: Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation